Awareness and knowledge of dental advertising guidelines among dental graduates in Malaysia / Ong Vivian - Ong , Vivian (2024)
Introduction: Unethical advertising is still the third most common case investigated by Malaysian Dental Council (MDC). This puts the offending dental practitioner at risk of receiving disciplinary action from the dental council such as temporary suspension of the practicing certificate, a penalty, or both. This risks the practitioner’s income and reputation. Furthermore, unethical advertisements have the potential to mislead the public. Many dental practitioners may be unaware or unclear about the advertising guidelines set by the MDC. Hence it is timely to investigate the knowledge of advertising guidelines among newly graduated dental practitioners as they represent the future of the profession. Objective: The objective of this study was to assess the level of awareness and knowledge of dental advertising guidelines among local dental graduates from the year 2023. Materials & Methods: This was a cross-sectional study using a survey instrument developed and validated for the purpose of this study using the Code of Professional Conduct Guidelines (CPC) and the Guidelines and Provisions for Public information (GPPI) as references. An initial sample size of 239 participants was calculated based on 95% confidence interval according to a finite population of 624. An additional of 15% was included to compensate for attrition rate, totalling the sample size requirement to 275. The questionnaire consisted of questions on participant demographics, a 5-point Likert scale to measure awareness, and seven knowledge domains: (1) Provision of dental information, (2) Display of fees, (3) Recommendation of specific products, (4) Online professionalism, (5) Description of clinic facilities and services, (6) Patient testimonials, and (7) Advertisement of specific treatment to measure their knowledge. The questionnaire was distributed via Google Forms to graduates from eight local dental schools using cluster sampling to ensure proportionate representation from public and private dental schools from different regions in Malaysia. Results: A total of 253 participants responded to the questionnaire (92%). The awareness of the public universities was significantly higher than their private counterparts (p-value < 0.05). The mean knowledge score was 61.8%. The domain with the highest knowledge score was ‘Online professionalism’ (71.30%). The domain with the lowest knowledge score was ‘Recommendation of specific products’ with only 46.77%. Independent t-test reported significant results (p-value < 0.05) between public and private dental graduates for ‘Description of clinic facilities’ and ‘Advertisement of specific treatment’. There was no gender predilection for the knowledge attained. Conclusion: This study concludes that there is an imbalance of advertising awareness and knowledge among university graduates from public and private institutions especially in specific knowledge domains. (410 words)